2022
DOI: 10.3390/cancers14153640
|View full text |Cite
|
Sign up to set email alerts
|

Bone-Targeted Agents and Metastasis Prevention

Abstract: The use of bone-targeted treatments has transformed the clinical care of many patients with metastatic breast cancer. In addition, due to the profound effects of bisphosphonates and denosumab on bone physiology and the bone microenvironment, the potential of bone-targeted agents to modify the process of metastasis has been studied extensively. Many adjuvant trials with bisphosphonates in early breast cancer have been performed. Variable outcomes in terms of disease recurrence have been reported, with any treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…During weight-bearing or resistance training, the force can be transmitted through the bones and converted into recognizable mechanical signals and cause a series of biochemical reactions to increase bone deposition, thereby increasing bone density and improving osteoporosis in patients [ 37 , 38 ]. Multiple studies [ 30 , 33 , 34 , 39 ] have shown that bone-modifying drugs such as bisphosphonates and denosumab are effective drugs to prevent and treat SREs and CTIBL. This study shows that oncology nurses have insufficient awareness of weight-bearing or resistance training and bone-modifying drugs to prevent bone loss and maintain bone health.…”
Section: Discussionmentioning
confidence: 99%
“…During weight-bearing or resistance training, the force can be transmitted through the bones and converted into recognizable mechanical signals and cause a series of biochemical reactions to increase bone deposition, thereby increasing bone density and improving osteoporosis in patients [ 37 , 38 ]. Multiple studies [ 30 , 33 , 34 , 39 ] have shown that bone-modifying drugs such as bisphosphonates and denosumab are effective drugs to prevent and treat SREs and CTIBL. This study shows that oncology nurses have insufficient awareness of weight-bearing or resistance training and bone-modifying drugs to prevent bone loss and maintain bone health.…”
Section: Discussionmentioning
confidence: 99%
“…Current therapies for bone metastases are aimed at relieving pain and lowering the risk of fracture in the affected bone. The treatment consists of radiation, bisphosphonates, and RANKL inhibitors [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Bone targeted agents such as the bisphosphonates, which have profound effects on bone cell function and modify the bone microenvironment, have been studied in numerous randomized clinical trials for more than two decades. However, variable results have been observed and the use of adjuvant bisphosphonates in women with early breast cancer remained an area of controversy (2).…”
mentioning
confidence: 99%